The Impact of Rentietrism on Authoritarian Durability in the Gulf - Shawki, Nadine (AUC Knowledge Fountain, 2024)
ABSTRACT Ever since its discovery, oil and its rents have strongly impacted the development of the Gulf states. The debate on whether oil has been a blessing or a curse to those states has been a prevailing topic in the literature, with an abundance of available data on the relationship between the durability of authoritarianism in the Gulf region and rentierism. The literature has long claimed that the legitimacy of Gulf rulers is secured through rent distribution, a concept known as Rentier State Theory (RST). With the leaders of Gulf nations being the “owners” of the oil reserves, they have been considered to use such a privilege to enhance their power, ensure their legitimacy, and prevent any change in the status quo. However, many scholars have criticized RST and pinpointed other variables impacting authoritarianism, at the forefront of which are ruling family participation and elite co-optation. In recent years, the literature has shifted to analyze how oil rents/wealth in the Gulf states are currently used to foster economic growth in all fields and elevate the living standards of their citizens, and how the visions of the Gulf leaders have pivoted toward diversifying and opening up their economies. In this context, this thesis contributes to the literature examining the relevance of rentierism in the Gulf states today by utilizing a comparative approach, considering the United Arab Emirates and Qatar as its two case studies. By comparing the recent developments in these countries’ respective political and economic systems, this thesis examines the roles of rentierism, as well as ruling families and the elite, to analyze the main variable still behind the persistent authoritarianism in the region. Keywords: Rentierism, Oil rents, Oil curse, Authoritarian durability, Gulf states, Ruling family participation, Elite co-optation.